Measurement of Transportation Service Quality- Taxi within Holy Makah City in Hajj & Umrah seasons between Reality and Expectation - Aldubayan, Eman Abdullah (Journal of Economic, Administrative and Legal Sciences, 2021)
The current study aimed to measure the quality of transportation service for pilgrims, Umrah performers, and visitors by taxi within the city of Makah Al-Mukarramah from the point of view of the beneficiary customers, and to achieve this goal and the sub-objectives emanating from it. The descriptive approach was used, where the questionnaire based on the standards of the Saudi Transport Authority for taxis of all three types: regular, family, and taxis for people with disabilities and the elderly was applied to a simple random sample of the study subjects, and the study data was analyzed using the statistical analysis program in the statistical package. (SPSS), and employing appropriate statistical methods, and the main problem in this study lies in what are the quality standards for taxi transport service within Makah Al-Mukarramah? Do these standards match reality and achieve the hope? And then the importance of the study is limited to seeking to identify the most important ways that must be available in taxis in particular and ways of transportation in general within the city of Makah Al-Mukarramah to facilitate trips and religious tourism for visitors to the House of God. The study revealed many results that contribute to the development of the transportation service for pilgrims and Umrah pilgrims in the city of Makah Al-Mukarramah during the Hajj and Umrah seasons in the future. Among the most important of these results, it was found that with regard to the availability of the technical specifications of the taxi, which were determined by the Technical Specifications Authority at the Ministry of Transport, there are only three technical specifications that were available to a large extent, and they include: taxi doors, taxi windows, and the quality of adaptation inside the taxi, The results also revealed that the majority of taxis inside the city of Mecca do not apply the technical standards set. The results also showed that the majority of technical equipment is not available in the taxi during the Hajj and Umrah seasons. The results also showed that the general level of customer satisfaction and that of the three areas of satisfaction is moderately available. The study recommended the absolute necessity for both the car company and the vehicle drivers to follow all means of technology and high technologies to provide visitors with the highest and most efficient transportation services. The study also recommended that companies should be charged with employing anyone who is sure that he has experience and high efficiency in managing the business assigned to them. In general, the study recommended applying everything related to the comfort of the passenger and his family members and adhering to the standards of quality and safety inside the vehicles.